2016
DOI: 10.1183/13993003.01945-2015
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease and risk of mortality in COPD

Abstract: Patients with chronic obstructive pulmonary disease (COPD) have higher incidence and prevalence of other chronic inflammatory diseases, including inflammatory bowel disease (IBD). We assessed whether IBD onset increases mortality risk in patients with COPD or asthma-associated COPD.Two population-based cohorts of COPD and asthma-COPD subjects were identified using the administrative health databases in Québec, Canada, 1990-2007. Death records were retrieved from the death certificate registry. Cox proportional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…We identified 458 studies from different databases and society meetings; 9 of them were selected after screening. Five studies were excluded with reason [2630] and four were included for the qualitative and quantitative analysis; three were published papers [18, 31, 32] and one was a meeting abstract [33]. Figure 1 describes the summary of the literature search according to PRISMA standards.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 458 studies from different databases and society meetings; 9 of them were selected after screening. Five studies were excluded with reason [2630] and four were included for the qualitative and quantitative analysis; three were published papers [18, 31, 32] and one was a meeting abstract [33]. Figure 1 describes the summary of the literature search according to PRISMA standards.…”
Section: Resultsmentioning
confidence: 99%
“…Population based studies have identified an increased prevalence of IBD in patients with COPD, and an increased risk of mortality in patients with both COPD and CD ( 13 15 ). Furthermore, the risk of COPD patients developing either CD or UC is increased by 2.72 and 1.83, respectively, compared to healthy controls ( 13 ), results that have been confirmed in additional populations ( 16 ).…”
Section: Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…Interdisciplinary Perspectives on Infectious Diseases bowel disease (IBD) also have a higher prevalence of pulmonary diseases [56][57][58]. Moreover, a recent study reported the association of fecal microbiota with bronchiolitis in infants where the authors identified four distinct fecal microbiota profiles (Escherichia, Bifidobacterium, Enterobacter/Veillonella, and Bacteroides) as dominant taxa and also the association of Bacteroides with a higher likelihood of bronchiolitis [59].…”
Section: Gut-lung Axismentioning
confidence: 99%